Measuring the efficiency of listed housing sector companies using the data envelopment approach in India / Bhawna Malhotra and Neelam Dhanda - Malhotra, Bhawna; Neelam Dhanda, Neelam (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2020)
The purpose of this study was to assess the technical efficiency and productivity of listed Housing sector companies in India, from 2008 to 2017. The study employed the Data Envelopment Approach (DEA) to examine the efficiency of the selected sample. The Malmquist Productivity Index was used to reveal the productivity change in Housing companies over the specified time. The study found little productivity growth among the Decision Making Units (DMUs) in spite of their efficiency improvement practices during the study period. The study indicates that there is a need for better utilization of resources and scale expansion. Further improvements in the housing sector can be achieved by technological improvements as it is the main reason behind poor productivity growth during the study period.